Contested Terrain: Attitudes of Lakota People towards Interpretation at Wind Cave National Park. Issue 1 (April 2019) - Smaldone, Dave; Rossi, Adam
Wind Cave National Park (NP) in South Dakota has a long and complex history with local indigenous peoples, including the Lakotas. Wind Cave is the location of the Lakotas' traditional origin story, and is now protected by a park representing a federal government that many indigenous peoples view negatively. The purpose of this exploratory study was to understand the attitudes of Lakotas toward Wind Cave NP and the interpretive stories it shares with visitors. Seventeen in-person interviews were conducted with Lakota people to understand their thoughts and feelings. Content analysis was used to uncover positive and negative themes about the park and various forms of interpretation. Findings indicate that park interpretation should include more Native perspectives, and recommendations are noted. The park should attempt to work more closely with Lakota and other local tribes, and can follow the examples of other National Park Service sites to accomplish these changes.